STEP TO CIVIL SOCIETY (ON HISTORICAL ROLE OF JUDICIAL REFORM OF 1864) - A D Popova (RUDN Journal of Russian History, 2014)
The article deals with the importance of the judicial reform of 1864 for the course of Alexander's modernization and analyzes the role of the judicial reforms for various aspects of life in the post-reform Russia. There is used a wide range of sources - archival materials, memoirs of contemporaries of that period, publications of periodicals. The author concludes that the judicial reform of 1864 should be considered as a significant step towards civil society. The analysis of the sources shows that the judicial reform of 1864 contributed to the increase in the protection of human rights and freedoms. The activities of new courts changed the public consciousness - in the society there was growing representation of rule of law, necessity to respect the rights and freedoms of others, to meet obligations. The judicial reform played a major role in the process of merging classes, the development of market relations. Thus, the introduction of the controversial independent public trial not only improved the justice, but was also an important step in the formation of civil society in Russia.